2021
DOI: 10.1016/j.heliyon.2021.e07910
|View full text |Cite
|
Sign up to set email alerts
|

Fruits of Vitex doniana sweet: toxicity profile, anti-inflammatory and antioxidant activities, and quantification of one of its bioactive constituents oleanolic acid

Abstract: Background: Vitex doniana Sweet fruit, an under-utilised crop specie of Ghana, has not been validated for its ethnomedical use in managing inflammatory conditions. Therefore, the study sought to investigate its antiinflammatory and antioxidant activities as well as isolate and quantify one of its active constituents. Materials and methods: In-vivo anti-inflammatory activity of the methanol fruit extract was evaluated using the carrageenan-induced oedema model in chicks. The in-vitro antioxidant property was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…This anti-inflammatory mechanism of the bioactive fraction could be explained by the up-regulation of COX-2 and the inhibition of prostaglandin and nitric oxide synthesis [ 40 ]. These results corroborate previous findings of the good anti-inflammatory activity of the ethyl acetate fraction of V. doniana [ 8 ]. In this study, a formalin test was also performed to assess whether the action of V. doniana EAF is central or peripheral.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This anti-inflammatory mechanism of the bioactive fraction could be explained by the up-regulation of COX-2 and the inhibition of prostaglandin and nitric oxide synthesis [ 40 ]. These results corroborate previous findings of the good anti-inflammatory activity of the ethyl acetate fraction of V. doniana [ 8 ]. In this study, a formalin test was also performed to assess whether the action of V. doniana EAF is central or peripheral.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, some studies shown that phytochemical analysis of the different parts of the plant extract revealed the presence of saponin, tannins, phenols, cardiac glycosides, flavonoids, sterols and triterpenes [ 48 ]. Thus, ethyl acetate fractionation (EAF) contributes to an optimisation of the chemical profile (phenolic, flavonoids), antioxidants and correlates positively with anti-inflammatory activity [ 8 ]. Such phytonutrient aggregate would be an excellent nutraceutical against inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sub-fraction F5B was also column chromatographed on sephadex LH-20 using CHCl 3 : MeOH (1:1) as the eluent to give compound 3 (0.94 g, 0.035%). Compound 4 (0.75 g, 0.028%) was obtained after subjecting sub-fraction F5C to column chromatography on sephadex LH-20 using CHCl 3 : MeOH (1:1) as the eluent [ 29 ].…”
Section: Methodsmentioning
confidence: 99%